The Effect Of Different Training Methods On The Biomotoric and Respiratory Parameters Of Adolescent Swimmers - Hürmüz Koç; Sıla Atalayın; Hüseyin Özden Yurdakul (Selcuk University, 2021)
Aim: In this study, the effect of water and terabant training with flipper outside water on selected physiological and biomotoric properties of adolescent swimmers was investigated. Method: The volunteers who participated in the study on the basis of their personal identifying information were randomly divided into two groups as training and control groups. The 38 volunteers in the training group participated in the training program for eight weeks, 19 of them used hand flippers inside water three days a week (n=19) while 19 of them used thera-bands outside water three days a week (n=19). The participants using hand flippers, swam along 25 meters long lanes in the swimming pool for 8x25m, 4x100m 4x200m, 4x100 and 4x25m. The participants using thera-bant outside water make 12 repetitions with yellow resistance bands for 3 sets. The volunteers in the control group (n=19) participated in swimming training only. Height, body weight, respiratory functions, strength and flexibility parameters were measured and the data were evaluated in SPSS 22.0 statistical package program. The t-test was used to determine the difference between before-training (BT) and after-training (AT) measurements. p lt;0.05 was considered as statistically significant. Results: The differences between the variables of flexibility, back strength, leg strength, hand grip strength, vital capacity, forced vital capacity and forced expiratory volume were statistically significant before and after the training. Conclusion: In conclusion, regular swimming exercises were found to be effective in the development of physiological and biomotoric characteristics of the children.